Imagens na história do vestuário : cânones e sintomas na obra Três Séculos de Modas (1923) - SOARES, Fernando Augusto Hage (Universidade Federal do Pará, 2022)
This thesis seeks to undertake an analysis of the illustrated clothing history, highlighting the role of images in this field of study. The research had as a triggering object for questions the book Três Séculos de Modas/Three Centuries of Fashions, by João Affonso, published in 1923, whose images were analyzed through symptoms present in its set of 56 authorial illustrations. The text is divided into four sections: the first is dedicated to listing the main theoretical meanings that influenced the critical and investigative process, analyzing aspects of clothing and its visual aspects, historical conceptions in the field of art and clothing, notions of anachronism and assembly as a method. From these bases, the second part deals with accessing data on the canons of clothing history, discussed by several authors, mapping a set of 35 works located in digital collections referenced for consultation, which were divided into the following categories: clothing books, costume books, prints and customs, romantic/historicist books, modern books. In the third part, the analysis of the pioneering work in Brazil is presented, presenting considerations about its diffusion, locating its characters and the book within the previous historiography, in order to carry out the analysis of its images via the assembly process, where identified symptoms were examined in the set of illustrations (by the perception of postures, gestures, objects, silhouettes), which generated the following interpretation categories: Armored; Expressive; Grace; Fashionable; Essential Woman; Comfortable; Conformist; Modern Dandy. Such categories demonstrate ways of representing emotions and mentalities about fashion in Três Séculos de Modas, which can be understood as survivals, which had their aspects discussed in the text and could be used in other research. Finally, in the last topic, a historical approach was carried out on the illustrated books of clothing history published in Brazil, highlighting some titles by Brazilian and foreign authors, moving towards the so-called visual guides, and ending the thesis with a chronological analysis that seeks to list the set of publications in this field of study in Brazil until 2019.